Biological screening of selected traditional medicinal plants species utilized by local people of Manokwari, West Papua Province - OBED LENSE (Nusantara Bioscience, 2011)
Abstract. Lense O. 2011. Biological screening of selected traditional medicinal plants species utilized by local people of Manokwari, West Papua Province. Nusantara Bioscience 3: 145-150. The aim of the research was to determine the presence of alkaloids and anti-microbial activity in extracts from selected medicinal plants from Manokwari District, West Papua, Indonesia. The method of alkaloid testing followed the standard phytochemical methods. The procedure of the Calibrated Dichotomous Sensitivity (CDS) test was used for the antimicrobial bioassays. Results of biological screening suggested that all but one of the 56 species tested contained different levels of alkaloids. Eleven species showed anti-microbial activity using bioassays of responses to two bacteria, Salmonella typhi and Klebsiella pneumoniae, and two fungi Candida albicans, and Cryptococcus neoformans; none of the plant extracts showed an antimicrobial effect against the bacteria Escherichia coli. Extract of Planconella sp. was the most active one as it showed activity against three different organisms (C. albicans, C. neoformans, and S. typhi).